Intracellular Ca2+ threshold reversibly switches flagellar beat off and on. Issue 5 (8th June 2018) - Sánchez-Cárdenas, C; Montoya, F; Navarrete, F A; Hernández-Cruz, A; Corkidi, G; Visconti, P E; Darszon, A
Abstract: Sperm motility is essential for fertilization. The asymmetry of flagellar beat in spermatozoa is finely regulated by intracellular calcium concentration ([Ca 2+ ]i ). Recently, we demonstrated that the application of high concentrations (10–20 μM) of the Ca 2+ ionophore A23187 promotes sperm immobilization after 10 min, and its removal thereafter allows motility recovery, hyperactivation, and fertilization. In addition, the same ionophore treatment overcomes infertility observed in sperm from Catsper1 −/−, Slo3 −/−, and Adcy10 −/−, but not PMCA4 −/−, which strongly suggest that regulation of [Ca 2+ ]i is mandatory for sperm motility and hyperactivation. In this study, we found that prior to inducing sperm immobilization, high A23187 concentrations (10 μM) increase flagellar beat. While 5–10 μM A23187 substantially elevates [Ca 2+ ]i and rapidly immobilizes sperm in a few minutes, smaller concentrations (0.5 and 1 μM) provoke smaller [Ca 2+ ]i increases and sperm hyperactivation, confirming that [Ca 2+ ]i increases act as a motility switch. Until now, the [Ca 2+ ]i thresholds that switch motility on and off were not fully understood. To study the relationship between [Ca 2+ ]i and flagellar beating, we developed an automatic tool that allows the simultaneous measurement of these two parameters. Individual spermatozoa were treated with A23187, which is then washed to evaluate [Ca 2+ ]i and flagellar beat recovery using the implemented method. We observe that [Ca 2+ ]i must decrease below a threshold concentration range to facilitate subsequent flagellar beat recovery and sperm motility. Abstract : A novel semiautomatized tool that simultaneously monitor [Ca 2+ ]i and motility reveals the requirement of a [Ca 2+ ]i threshold for flagellar beating control.